A imagem e identidade profissional do assistente social expressas no cotidiano : um estudo a partir da demanda de trabalho na alta complexidade em saúde - Silva, André Luis da (2016)
The present thesis systematizes the study carried out on the image and the professional identity of the social worker and the relation with the demands reported to the profession in the Hospital de Clínicas de Porto Alegre (HCPA), locus of accomplishment of the study. The historical line of institutionalization of Social Work in its 80 years of existence in Brazil presents to society a profession endowed with a plurality of images and professional identities that vary from coercion and consensus to the profession that fights for social transformation. The research resulting from this production aimed to analyze the relationship between the demands directed to the social worker in the hospital area and the image and the professional identity of the Social Work with a view to pointing out the particularities of the professional work in the high complexity in health. The research was guided by the dialectical-critical method, with a mixed approach, through the technique of documentary analysis to collect data that were interpreted in the light of content analysis (BARDIN, 1979). It was identified that the professional demands directed to the Social Work in the HCPA can be divided into three main groups: i) expressions of inequality experienced by the subjects; ii) measures and services related to the Health Services network, between sectors and at home; iii) patient and / or family follow-up procedures. The systematization of the data and the analysis allow the thesis that the demands sent to the Social Work reflect the image of the profession that is a constituent part of their professional identity, since in their dialectical relation the appearance (the image) reveals aspects of its essence (identity). It can be said that the social worker is the professional demanded to be the link between the users and the institution, the users and the network of services, and also between the institution and the service network. In addition, in his daily work, the social worker has contact with demands, often seemingly simple or displaced from his ethical-political project, but which require a chain of mediations so that provisions and procedures can be leveraged from more social processes from the perspective of guaranteeing rights.